Aortic valve replacement vs. conservative treatment in asymptomatic severe aortic stenosis: long-term follow-up of the AVATAR trial - Banovic, Marko; Putnik, Svetozar; Da Costa, Bruno R; Penicka, Martin; Deja, Marek A; Kotrc, Martin; Kockova, Radka; Glaveckaite, Sigita; Gasparovic, Hrvoje; Pavlovic, Nikola; Velicki, Lazar; Salizzoni, Stefano; et al. (European heart journal, 2024)
BACKGROUND AND AIMS: The question of when and how to treat truly asymptomatic patients with severe aortic stenosis (AS) and normal left ventricular (LV) systolic function is still subject to debate and ongoing research. Here, the results of extended follow-up of the AVATAR trial are reported (NCT02436655, ClinicalTrials.gov). METHODS: The AVATAR trial randomly assigned patients with severe, asymptomatic AS and LV ejection fraction ≥ 50% to undergo either early surgical aortic valve replacement (AVR) or conservative treatment with watchful waiting strategy. All patients had negative exercise stress testing. The primary hypothesis was that early AVR will reduce a primary composite endpoint comprising all-cause death, acute myocardial infarction, stroke, or unplanned hospitalization for heart failure (HF), as compared with conservative treatment strategy. RESULTS: A total of 157 low-risk patients (mean age 67 years, 57% men, mean Society of Thoracic Surgeons score 1.7%) were randomly allocated to either the early AVR group (n = 78) or the conservative treatment group (n = 79). In an intention-to-treat analysis, after a median follow-up of 63 months, the primary composite endpoint outcome event occurred in 18/78 patients (23.1%) in the early surgery group and in 37/79 patients (46.8%) in the conservative treatment group [hazard ratio (HR) early surgery vs. conservative treatment 0.42; 95% confidence interval (CI) 0.24-0.73, P = .002]. The Kaplan-Meier estimates for individual endpoints of all-cause death and HF hospitalization were significantly lower in the early surgery compared with the conservative group (HR 0.44; 95% CI 0.23-0.85, P = .012, for all-cause death and HR 0.21; 95% CI 0.06-0.73, P = .007, for HF hospitalizations). CONCLUSIONS: The extended follow-up of the AVATAR trial demonstrates better clinical outcomes with early surgical AVR in truly asymptomatic patients with severe AS and normal LV ejection fraction compared with patients treated with conservative management on watchful waiting.
Keywords: Aortic stenosis; Aortic Valve; Avatar; hospitalizace; Follow-Up Studies; Hospitalization; aortální chlopeň; Watchful Waiting; následné studie; Aortic valve surgery; asymptomatické nemoci; lidé středního věku; výsledek terapie; Heart Valve Prosthesis Implantation; konzervativní terapie; ženské pohlaví; pozorné vyčkávání; lidé; Low-risk; chirurgická náhrada chlopně; tepový objem; Aortic Valve Stenosis; mužské pohlaví; Asymptomatic Diseases; senioři; Stroke; Treatment; Treatment Outcome; avatar; Aged; Humans; Asymptomatic; Conservative Treatment; Female; Male; Middle Aged; Outcomes; aortální stenóza; cévní mozková příhoda; Stroke Volume